PEMANFAATAN INSTAGRAM DALAM MENJAGA HUBUNGAN BAIK PT. PUPUK KUJANG DENGAN STAKEHOLDERS - Rahayu, Maretha Nadya; Poerana, Ana Fitriana; Lubis, Fardiah Oktariani (Universitas Prof. Dr. Moestopo (Beragama), 2020)
The development and advancement of technology today has brought many changes to daily life, including in public relations activities. One of them is Corporate Communication of PT. Pupuk Kujang, which is required to be able to take advantage of new media such as social media. Corporate Communication of PT. Pupuk Kujang use Instagram social media in public relations activities, especially in building good relationships with its stakeholders. This study aims to determine how the Corporate Communication of PT. Pupuk Kujang use Instagram media to build good relationships with stakeholders. This study uses a qualitative method with the concept of Media Richness Theory to measure the ability or wealth of Instagram media through the available features. The paradigm used was constructivism and data collection used interviews and non-participant observation. The research results show that the Corporate Communication of PT. Pupuk Kujang has made good use of Instagram media. Corporate Communication forms a team that is responsible for managing social media, to organize and create all content on social media including Instagram. To attract the attention and trust of stakeholders, Corporate Communication always has new innovations to keep up with the times. Contents presented on the innstagram of PT. Pupu ujang is very diverse to suit its stakeholders. And when viewed from Media Richness Theory, Instagram is included in the rich media class because it meets all Media Richness criteria.Â